Efficiency Increase in Liquefied Natural Gas Production at Motor Gas Filling Compressor Station using Propane-Butane Fraction pre- Extraction - 10.52254/1857-0070.2023.1-57.07; Lebedev M.S. (Problems of the Regional Energetics)
Nowadays the production of liquefied natural gas including low-tonnage production is one of the most promising areas of modern energy. The development of measures to improve the quali-ty of a liquefied product and the efficiency of its production processes is an urgent scientific problem of great practical importance. The aim of the study is to develop an effective techno-logical scheme, which allows improving the quality of liquefied natural gas produced at auto-mobile gas filling compressor stations. The goal was achieved by performing an analysis of the effectiveness of the natural gas components low-temperature separation process at a gas distri-bution station before its liquefaction at the compressed natural gas filling station in order to ob-tain a product with a reduced content of heavy hydrocarbons, as well as through a practical study of the process of low-temperature separation of hydrocarbons at an operating liquefaction facility natural gas. According to these characteristics and conducted experimental studies, the effectiveness of the scheme for obtaining a propane-butane product in the process of liquefying natural gas has been confirmed. An important result is also a new substance obtained during the experiments, which has the properties of degreasing. The significance of the results obtained lies in the possibility of their use in the design of subsequent facilities for the reduction and lique-faction of natural gas with a line for the production of propane-butane and the investigated de-greasing agent.